2001
DOI: 10.1111/j.1348-0421.2001.tb01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus Accessory Proteins as Interferon Antagonists

Abstract: A new role of the Paramyxovirus accessory proteins has been uncovered. The P gene of the subfamily Paramyxovirinae encodes accessory proteins including the V and/or C protein by means of pseudotemplated nucleotide addition (RNA editing) or by overlapping open reading frame. The Respirovirus (Sendai virus and human parainfluenza virus (hPIV)3) and Rubulavirus (simian virus (SV)5, SV41, mumps virus and hPIV2) circumvent the interferon (IFN) response by inhibiting IFN signaling. The responsible genes were mapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 125 publications
(174 reference statements)
4
73
0
3
Order By: Relevance
“…Both RSV and hMPV were shown to interfere with the IFN cascade and to inhibit IFN production in the lung (Guerrero-Plata et al, 2005). It is suggested that the non-structural proteins NS1 and NS2 of RSV and the G protein of hMPV are responsible for the resistance to IFN-α, by inhibiting the effect of antiviral proteins including MxA or by targeting signalling pathways such as the RIG-I-dependent gene transcription (Schlender et al, 2000;Gotoh et al, 2001;Leyrat et al, 2014). We were able to show that the down-regulation of IFN-α mRNA expression was more prominent in CTOC than in TTOC.…”
Section: Discussionmentioning
confidence: 99%
“…Both RSV and hMPV were shown to interfere with the IFN cascade and to inhibit IFN production in the lung (Guerrero-Plata et al, 2005). It is suggested that the non-structural proteins NS1 and NS2 of RSV and the G protein of hMPV are responsible for the resistance to IFN-α, by inhibiting the effect of antiviral proteins including MxA or by targeting signalling pathways such as the RIG-I-dependent gene transcription (Schlender et al, 2000;Gotoh et al, 2001;Leyrat et al, 2014). We were able to show that the down-regulation of IFN-α mRNA expression was more prominent in CTOC than in TTOC.…”
Section: Discussionmentioning
confidence: 99%
“…The former conclusion was drawn from experimental results achieved mainly with mutated recombinant SeV-infected cells, in which the anti-IFN ability of the mutant C proteins would be affected by many factors, including other viral proteins, autocrine IFN associated with infection, and the expression level of the mutant C protein at the time of IFN treatment. It is possible that these factors might have led to the discrepancy (16,17). In contrast to the STAT degradationindependent mechanism presented here, Garcin et al emphasized the degradation of STAT1 in SeV-infected MEF cells as an SeV blocking mechanism for IFN signaling and attempted to find the common denominator between functions of SeV C protein and rubulavirus V proteins (10,11,13,30).…”
Section: Fig 8 Stat1mentioning
confidence: 99%
“…This finding had suggested crucial roles of the V and C proteins in a virus life cycle, although their roles had remained an enigma for a long time. Several lines of evidence have accumulated, however, demonstrating that the accessory proteins form a group of antagonists against the host immune system (9,(15)(16)(17). The Paramyxovirinae family contains three genera: Rubulavirus, Respirovirus, and Morbillivirus.…”
mentioning
confidence: 99%
“…However, there is increasing evidence that P, W, or C proteins of paramyxoviruses including NiV, MeV, and SeV play important roles in IFN antagonism by distinct mechanisms. Thus, it seems that most if not all P gene accessory proteins have evolved for roles in immune evasion as important pathogenicity factors [24][25][26][27][28] . Consistent with important roles in infection, V proteins show high conservation in the unique C-terminal region ( Figure 2) [29][30][31] , including absolute conservation of seven conserved cysteine residues and a histidine, which form a zinc-finger domain (highlighted in Figure 2).…”
Section: Paramyxovirus P Genementioning
confidence: 99%